(untitled) (Филолошки студии, 2019)
The historical novel, together with its different subgenre variants, is a kind of constant in the literary-historical development of the recent Slovenian fiction. Its unalterable persistence within the genre system of the Slovenian literature and wider, could be explained by the ability of the genre to adapt to the needs of the contemporary reality and the individual over and over again. Therefore, over the last few decades, it has been possible to notice a kind of revision and inovation of the traditional form of the historical novel in the Slovenian literature, with the key role of the changed relation towards history, different elaboration and status of the theme, as well as the type of character, i.e. subject of the represented historical events. The representative example of the new paradigmatic characteristics of this genre is without any doubt the novel Minuet for Guitar by Vitomil Zupan.